Comparative study of the key aromatic compounds of Cabernet Sauvignon wine from the Xinjiang region of China - Yao, Yao (J Food Sci Technol, 2021)
To determine the differences in the characteristic volatile compounds between winemaking areas in the Xinjiang region, this study was conducted by sampling Cabernet Sauvignon grapes from four winemaking areas in Xinjiang, named Tianshanbeilu, Yili, Yanqi, and Hami. After undergoing the same alcoholic fermentation treatment, the wines from the four areas were subjected to GC–MS and sensory analysis. The results showed that fifty aromatic compounds (including higher alcohols, esters, acids, terpenes, aldehydes/ketones, et al.) were identified and quantified. Interestingly, the terpene and phenylalanine derivative contents of the wines from northern Xinjiang were higher than those from the south. Additionally, four vineyards highly contributed to the development of key volatile compounds in the Xinjiang region. Sensory analysis showed that the wines from northern Xinjiang were impressive with a flowery and fruity aroma and the wines from southern Xinjiang had a stronger wine body and astringency.